Periconceptional use of vitamin A and the risk of giving birth to a child with nonsyndromic orofacial clefts—A meta‐analysis. Issue 10 (31st March 2022) - Alade, Azeez; Ismail, Wesam; Nair, Rajeshwari; Schweizer, Marin; Awotoye, Waheed; Oladayo, Abimbola; Ryckman, Kelli; Butali, Azeez
Abstract: Background: We conducted a meta‐analysis of observational epidemiological studies to evaluate the association between periconceptional use of vitamin A and the risk of giving birth to a child with nonsyndromic orofacial clefts (NSOFCs). Methods: We carried out a systematic literature search of Embase, PubMed, Web of Science, Google Scholar, and OpenGrey from inception to June 30, 2021. Two reviewers independently evaluated the studies that met the inclusion criteria and filled out an abstraction form for each study. Study quality was assessed using the Newcastle‐Ottawa Assessment Scale (NOS). Adjusted estimates were pooled with an inverse variance weighting using a random‐effects model. Heterogeneity and publication bias were assessed using the Cochran's Q test and funnel plot, respectively. Results: A total of six case–control studies with moderate risk of bias were included. The pooled OR showed a 20% reduction in the risk of NSOFCs for periconceptional use of vitamin A which was not statistically significant (OR = .80; 95% CI .54–1.17, p  = .25). For nonsyndromic cleft lip with or without cleft palate (NSCL/P), the studies were homogenous, and the pooled estimate showed a 13% risk reduction, which was significant (OR = .87; 95% CI .77–.99, p  = .03). For nonsyndromic cleft palate only (NSCPO), the pooled estimate showed a 33% lower likelihood, which was not statistically significant (OR = .67; 95% CI .42–1.08, p  = .10). Conclusion: Our results suggest a possible protective effect for the periconceptional use of vitamin A on the risk of NSCL/P. This finding should be investigated further in prospective studies across multiple populations.